2021
DOI: 10.1038/s41531-021-00160-3
|View full text |Cite
|
Sign up to set email alerts
|

How COVID-19 will boost remote exercise-based treatment in Parkinson’s disease: a narrative review

Abstract: The lack of physical exercise during the COVID-19 pandemic-related quarantine measures is challenging, especially for patients with Parkinson’s disease (PD). Without regular exercise not only patients, but also nursing staff and physicians soon noticed a deterioration of motor and non-motor symptoms. Reduced functional mobility, increased falls, increased frailty, and decreased quality of life were identified as consequences of increased sedentary behavior. This work overviews the current literature on problem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
48
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(52 citation statements)
references
References 105 publications
(140 reference statements)
0
48
0
4
Order By: Relevance
“…In addition, fitness centers, dancing classes, and many other team sports that are popular among PD patients but also socio-cultural institutions (e.g., restaurants, art galleries) were closed over many months. This challenge has been discussed already early during the pandemic [6,7] and has ever since been corroborated by the literature [3,[8][9][10][11]. For instance, a Dutch group found that the pandemic evokes psychological distress and lifestyle changes including reduced physical activity [12].…”
Section: Introductionmentioning
confidence: 81%
“…In addition, fitness centers, dancing classes, and many other team sports that are popular among PD patients but also socio-cultural institutions (e.g., restaurants, art galleries) were closed over many months. This challenge has been discussed already early during the pandemic [6,7] and has ever since been corroborated by the literature [3,[8][9][10][11]. For instance, a Dutch group found that the pandemic evokes psychological distress and lifestyle changes including reduced physical activity [12].…”
Section: Introductionmentioning
confidence: 81%
“…e present findings indicate that home-based AO + MI training delivered using mobile technology is feasible in people with mild to moderate PD, although future work should explore the feasibility of the intervention in those with more severe symptoms or in different subtypes. Homebased approaches could provide widely accessible, low-cost, and scalable alternatives or supplements to existing rehabilitation programmes, and their importance is more apparent than ever in light of the COVID-19 pandemic [75,76].…”
Section: Proposed Mechanisms and Future Workmentioning
confidence: 99%
“…Bei diesen Patient*innen wird daher ein Rückgang des Therapiefortschritts, ein Fortschreiten von degenerativen Erkrankungen und Chronifizierungen von akuten Erkrankungen, wie zum Beispiel nach einem Schlaganfall oder einer Operation am Bewegungsapparat, befürchtet. Dies wird durch aktuelle Studien unterstützt [23] , [24] , [25] . Bei Patient*innen mit Morbus Parkinson beispielsweise wurde bereits eine Verschlechterung der Erkrankung durch eingeschränkte Mobilität und pandemiebedingte psychische Belastungen, wie Ängste und Einsamkeit, sowie eine dadurch deutlich reduzierte Lebensqualität festgestellt [24] , [25] .…”
Section: Diskussionunclassified
“…Dies wird durch aktuelle Studien unterstützt [23] , [24] , [25] . Bei Patient*innen mit Morbus Parkinson beispielsweise wurde bereits eine Verschlechterung der Erkrankung durch eingeschränkte Mobilität und pandemiebedingte psychische Belastungen, wie Ängste und Einsamkeit, sowie eine dadurch deutlich reduzierte Lebensqualität festgestellt [24] , [25] . Regelmäßige Physiotherapie scheint daher essentiell, um den Krankheitsverlauf und die Lebensqualität der Parkinsonpatient*innen positiv beeinflussen zu können.…”
Section: Diskussionunclassified
See 1 more Smart Citation